Pemaknaan Pengasuhan Berbasis Bimbingan dalam Mengembangkan Sosial-Emosional Anak Usia Dini: Studi Fenomenologis di TK Islam - Pepi Nuroniah; M. Solehuddin; Hayinah Rahayu (JEA (Jurnal Edukasi AUD), 2026)
This study explores educators’ understandings of guidance-based caregiving in Islamic kindergartens in Serang City, Indonesia, and how these understandings inform practices that support young children’s social-emotional development. While previous studies have mainly emphasized social-emotional learning (SEL) outcomes and intervention-based programs, limited attention has been paid to educators’ lived understandings of caregiving within specific religious and cultural contexts, particularly in Muslim-majority settings. Addressing this gap, the study examines how guidance-based caregiving is experienced, interpreted, and enacted by educators in an Islamic early childhood setting. A qualitative phenomenological approach was employed. Data were collected through in-depth interviews and non-participant observations involving two teachers and one principal at an Islamic kindergarten in Serang City, Indonesia. Descriptive phenomenological analysis was used to identify recurring meanings and synthesize the essence of educators’ caregiving experiences. The findings show that guidance-based caregiving is interpreted as a holistic process of mentoring children through practices of educating, caring, and guiding in daily interactions within a safe environment. This practice aligns with SEL competencies and is grounded in Islamic values as a source of morality and emotional regulation in early childhood education.